Peran Mahasiswa Asistensi Mengajar dalam Mewujudkan Sekolah Sehat (Apotek Hidup) - Lisa Ulandari; Arifatul Ulya, Shofia (Rengganis Jurnal Pengabdian Masyarakat, 2024)
The increase in morbidity and mortality rates from various diseases demands the need for efforts to improve public health, especially for students who have to do a lot of activities. Schools are one part of the community structure that requires attention to health aspects. Health problems that often occur in the school environment are the reason for the need to provide health measures such as medicines in the school environment. For this reason, Teaching Assistance students describe healthy schools by planting medicinal plants or what is known as the Living Pharmacy. Teaching Assistance is a program that provides students with the opportunity for 3.5 months to accompany teachers and school principals in carrying out learning activities. This activity aims to empower junior high school students to plant living pharmacies in their school environment as an effort to maintain environmental sustainability, especially the school environment. The activity methods include; providing land, preparing tools and materials, clearing land, planting various types of plants and caring for these plants. The result of this activity is the availability of a living pharmacy in the school environment consisting of various types of plants. The number of plant types found in the school's living pharmacy is 5 types of plants. Each plant has a marker containing the name of each plant to make it easier to recognize the type of plant